PERVALE-S: a new cognitive task to assess deaf people’s ability to perceive basic and social emotions - Mestre, José M.; Larrán, Cristina; Herrero, Joaquín; Guil, Rocío; de la Torre, Gabriel G. (Frontiers in Psychology, 2015)
PERVALE-S was developed to assess the ability of DP to perceive both social and basic emotions. PERVALE-S presents different sets of visual images of a real deaf person expressing both basic and social emotions, according to the normative standard of emotional expressions in Spanish sign language. Emotional expression stimuli were presented at two different levels of intensity (1: low; and 2: high) because DP do not distinguish the same range of frequency adverbs as hearing people (HP) do. Then, participants had to click on the more suitable emotional expression. PERVALE-S contains video instructions of a sign language interpreter to improve DP’s understanding about how to use the software. DP had to watch the videos before answering the items. To test PERVALE-S, a sample of 56 individuals was recruited (18 signers, 8 lip-readers, and 30 hearing people). Participants also responded to a personality test (HSPQ adapted) and a fluid intelligence measure (RAPM). Moreover, four teachers from deaf center rated all deaf participants. Results: there were no significant differences between DP and HP in performance in PERVALE-S. Confusion matrices revealed that embarrassment, envy, and jealousy were worse perceived by participants (DP and HP). There were not significant differences of emotional perception performance among lip-readings, signers, and hearings. Regarding emotional perception ability (EPA), basic emotion performance was positively related to consciousness, and negatively with tension. Social emotion performance was positively related to age and fluid intelligence, and negatively related to dominance. When an adapted instrument for assessing EPA is developed without language implications, the performance among DP and HP are closer. This instrument could have experimental interest in order of eliminating language influences in EPA.